PREDIKSI CHROMIUM RELEASE DARI BATAKO LIMBAH BUFFING PENYAMAKAN KULIT DENGAN SIMULASI MONTE CARLO - M. Wahyu Syabani (Politeknik ATK Yogyakarta, 2015)
Solid waste from buffing process in Leather Tanning Industries contains trivalent chromium salt. The trivalent chromium can be immobilized by using it as raw matexal in concrete manufacturing. Worst scenario was used in this chromium-r ease modeling also. The concrete was freely exposed to the environment and one side of the concrete was in continuous contact with water. The modeling result give us information that trivalent chromium can released to the body of the water, but it need long period until its concentration in water reached government regulation (l mg/L)